2010
DOI: 10.1002/ccd.22607
|View full text |Cite
|
Sign up to set email alerts
|

A novel catheter in patients with peripheral chronic total occlusions: A single center experience

Abstract: In this single center observational review, the Crosser device in peripheral CTO lesions had a procedural success of 41%. © 2010 Wiley-Liss, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 33 publications
0
17
0
1
Order By: Relevance
“…Al-Ameri et al [14] also reported the successful use of the Crosser device in all three cases. A recent single center observational review [15] has reported the Crosser device used in 25 consecutive patients with 27 CTOs, which had a poor procedural success of 41%. The overall procedural success with any device was reasonable (63%).…”
Section: 2mentioning
confidence: 98%
“…Al-Ameri et al [14] also reported the successful use of the Crosser device in all three cases. A recent single center observational review [15] has reported the Crosser device used in 25 consecutive patients with 27 CTOs, which had a poor procedural success of 41%. The overall procedural success with any device was reasonable (63%).…”
Section: 2mentioning
confidence: 98%
“…To overcome this problem, ultrasonic probes are combined with axially oscillating members to achieve both mechanical and ultrasonic disruption in the clinically available Crosser catheter (FlowCardia, Sunnyvale, CA; in use for peripheral chronic occlusions) [65,66] the currently abandoned UltraSound-driven Oscillating probe Aspirating Thrombectomy (US-OAT, Storz GmbH, Tuttlingen, Germany; abandoned, originally used for peripheral acute occlusions) device [67], as well as with antithrombotic agents in the EndoWave System (EKOS Corporation, Bothell, WA; under development for peripheral acute occlusions) which is currently under development [68]. In a study of Galassi et al [69], a success rate of 84.8% is described using Crosser catheter for recanalizing coronary chronic occlusions, with no periprocedural myocardial infarction, perforation or 30 day major adverse cardiac events.…”
Section: B) High-speed Impact Forcementioning
confidence: 99%
“…A variety of devices are available for CTO's, including specialty wires and dedicated CTO crossing devices [13,[15][16][17]. The technique or device used depends both on lesion characteristics and physician experience.…”
Section: Crossing the Lesion(s)mentioning
confidence: 99%